Investigation of covalently colored polyurethane latexes based on novel anthraquinone polyurethane chain extenders. Issue 1 (2nd January 2017) - Jin, Qingjun; Li, Botian; Zhang, Hong; Li, Lingxiao; Shen, Jie; Kan, Chengyou
ABSTRACT: Novel red and yellow polyurethane (PU) chain extenders with one anthraquinone chromophore and two hydroxyls were synthesized, and then used to fabricate covalently colored PU latexes with pendent chromophores on the PU backbone. The chemical structures of the chain extenders were characterized by 1 H-NMR and FTIR, and the properties of PU latexes and their films were investigated by UV-Vis absorption spectra, particle size analysis, FTIR, Soxhlet's extraction and xenon arc aging testing. Results showed that the covalently colored PUs had the same UV-Vis absorption behavior as the corresponding chain extenders, and amount of the chain extenders had no obvious influence on the latex preparation process and the resulted latex colloidal properties. Compared with the corresponding non-covalently colored PU latex films, both the light fastness and the solvent fastness of the covalently colored PU latex films were significantly enhanced by the covalent incorporation of chromophores with PU matrix.